Pole piece and preparation method thereof, battery and electric equipment
By adjusting the inner solid content gradient of the coating during the battery electrode sheet manufacturing process and uniformly controlling the solvent volatility rate, the problems of easy cracking and poor adhesive ability of the thick electrode sheet are solved, and an efficient and suitable electrode sheet preparation method is achieved.
Patent Information
- Application Number
- CN202411928512.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-04-29
AI Technical Summary
During the battery manufacturing process, thick electrode sheets are prone to cracking and have poor adhesive capacity, making it difficult to adapt to large-scale industrial production.
By adjusting the solid content gradient inside the coating, the solvent volatilization rate in the coating is uniform during the drying process, thereby preparing a pole sheet that is not prone to cracking. The specific method includes simultaneously coating the first slurry and the second slurry on the surface of the current collector and drying at a temperature of 50°C to 140°C. The difference between the solid content of the first slurry and the solid content of the second slurry is 3% to 7%.
It realizes that the pole sheet is not easy to crack while increasing the surface density, improves the adhesion ability and production adaptability of the pole sheet, and is suitable for large-scale industrial production.
Smart Images

Figure HDA0005209770250000011 
Figure HDA0005209770250000012 
Figure HDA0005209770250000013
Abstract
Description
Technical Field
[0001] The present application belongs to the field of battery technology, and specifically relates to a pole piece and a preparation method thereof, a battery and an electrical device. Background Art
[0002] In order to meet the needs of energy storage systems and electric vehicle markets for high energy density and fast charging, lithium-ion batteries with both high energy and high power density have received widespread attention. The thick electrode structure design can significantly improve the energy density of the battery and reduce costs, and is compatible with various electrode materials. It is one of the research hotspots for the development of high energy density lithium-ion batteries. However, thick electrodes usually face problems such as poor mechanical properties and slow reaction kinetics. In the related art, this has been improved by secondary drying or increasing the solid content of the slurry and adjusting the drying parameters, but this method has too low preparation efficiency, is not suitable for large-scale production, or has high requirements for equipment stability. Therefore, the problem of easy cracking of the pole piece still needs further improvement. Summary of the invention
[0003] This application is based on the inventor's discovery and understanding of the following facts and problems:
[0004] In the battery manufacturing process, it is necessary to prepare positive and negative pole pieces. The active material content (surface density) of the pole pieces will directly affect the capacity and capacity density of the battery. However, the pole pieces prepared directly by increasing the surface density will have defects such as easy cracking, poor adhesion, and inability to be industrialized. Usually, it is necessary to improve them through pole piece formula design, drying parameter optimization, pole piece structure design, etc. The inventors have found that in the pole piece production process, due to the increase in the thickness of the coating, more solvent needs to be volatilized inside the slurry after the solidification layer is formed on the surface during the drying process, so it is more likely to crack the pole piece. To solve this problem, the present application improves the problem of easy cracking of the pole piece by adjusting the solid content gradient inside the coating so that the solvent volatilization rate in the coating during the drying process is uniform.
[0005] The present application aims to solve one of the technical problems in the related art at least to a certain extent. To this end, the present application proposes a pole piece that is not easy to crack and a preparation method thereof, a battery and an electrical device.
[0006] The first aspect of the present application provides a method for preparing a pole piece, comprising:
[0007] Coating the first slurry and the second slurry simultaneously on at least one side of the current collector to obtain a first coating layer and a second coating layer;
[0008] Drying the first coating layer and the second coating layer so that the first coating layer and the second coating layer together form an active material layer to obtain the electrode sheet;
[0009] Wherein, the difference between the solid content of the first slurry and the solid content of the second slurry is 3% to 7%.
[0010] In the present application, the electrode is prepared by gradiently setting the solid content of the slurry, so that the electrode is not prone to cracking while increasing the surface density.
[0011] In some embodiments, the solid content of the first slurry ranges from 45% to 75%; in other embodiments, the solid content ranges from 55% to 65%.
[0012] In some embodiments, the viscosity of the first slurry is 1000 cps to 20000 cps; in other embodiments, the viscosity is 4000 cps to 8000 cps.
[0013] In some embodiments, the solid content of the second slurry ranges from 40% to 70%; in other embodiments, the solid content ranges from 50% to 60%.
[0014] In some embodiments, the viscosity of the second slurry is 500 cps to 15,000 cps; in other embodiments, the viscosity is 2,000 cps to 4,000 cps.
[0015] In some embodiments, the difference between the solid content of the first slurry and the solid content of the second slurry is 5%, thereby improving the problem of uneven solvent evaporation speed inside the coating.
[0016] In some embodiments, the first slurry and the second slurry each independently include an active material, a binder, a conductive agent, a dispersant, and a solvent.
[0017] In some embodiments, the dispersant includes at least one of sodium lauryl sulfate and fatty alcohol polyoxyethylene ether, thereby improving the dispersibility of the slurry and improving the viscosity of the slurry.
[0018] In some embodiments, based on the mass of the first slurry or the second slurry, the mass content of the dispersant is 0.2% to 0.4%, thereby improving the slurry viscosity while saving costs.
[0019] In some embodiments, the coating comprises at least one of blade coating, roller transfer coating, slot die coating, and double-layer extrusion coating.
[0020] In some embodiments, the drying temperature is 50° C. to 140° C. This helps to increase the drying rate.
[0021] The second aspect of the present application provides a pole piece, which is prepared by the method described in the first aspect of the present application. Thus, the pole piece is not prone to cracking while the surface density is increased.
[0022] The third aspect of the present application provides a battery, comprising a pole piece prepared by the method described in the first aspect of the present application or a pole piece described in the second aspect of the present application. Thus, the battery has a higher energy density.
[0023] The fourth aspect of the present application provides an electrical device, comprising the battery described in the third aspect of the present application. The electrical device has all the features and advantages of the battery described above, which will not be described one by one here. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 It is a schematic diagram of the structure of the pole piece of the embodiment of the present application.
[0025] Figure 2 It is a schematic diagram of double-layer extrusion coating in an embodiment of the present application.
[0026] Figure 3 This is a SEM photograph of the positive electrode sheet of Example 1 of the present application.
[0027] Figure 4 This is a SEM photograph of the positive electrode sheet of Example 2 of the present application.
[0028] Figure 5 This is a SEM photograph of the positive electrode sheet of Example 3 of the present application.
[0029] Figure 6 This is a SEM photograph of the positive electrode sheet of Comparative Example 1 of the present application.
[0030] Figure 7 This is a SEM photograph of the positive electrode sheet of Comparative Example 2 of the present application.
[0031] Reference numerals: 1 - current collector; 2 - first coating layer; 3 - second coating layer. DETAILED DESCRIPTION
[0032] The embodiments of the present application are described in detail below, and examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present application, but cannot be understood as limiting the present application.
[0033] The first aspect of the present application provides a method for preparing a pole piece, comprising:
[0034] S1: Coating the first slurry and the second slurry simultaneously on at least one side surface of the current collector to obtain a first coating layer and a second coating layer.
[0035] Specifically, the first active material can be mixed with the first binder, the first conductive agent and the dispersant, and a proper amount of solvent can be added to prepare a first slurry, and the second active material can be mixed with the second binder, the second conductive agent and the dispersant, and a proper amount of solvent can be added to prepare a second slurry.
[0036] In some embodiments, the solid content of the first slurry ranges from 45% to 75%; in other embodiments, the solid content is 55% to 65%. For example, the solid content of the first slurry can be 45%, 50%, 55%, 60%, 65%, 70% or 75%, etc. The solid content of the second slurry ranges from 40% to 70%; in other embodiments, the solid content is 50% to 60%. For example, the solid content of the second slurry can be 40%, 45%, 50%, 55%, 60%, 65% or 70%, etc.
[0037] The difference between the solid content of the first slurry and the solid content of the second slurry is 3% to 7%, for example, 3%, 4%, 5%, 6% or 7%. In some specific examples, the difference between the solid content of the first slurry and the solid content of the second slurry is 5%. This can improve the problem of uneven solvent evaporation speed inside the coating.
[0038] In some embodiments, the viscosity of the first slurry is 1000cps to 20000cps; in other embodiments, the viscosity is 4000cps to 8000cps. For example, the viscosity of the first slurry can be 1000cps, 2000cps, 3000cps, 4000cps, 5000cps, 6000cps, 7000cps, 8000cps, 9000cps, 10000cps, 15000cps or 20000cps.
[0039] In some embodiments, the viscosity of the second slurry is 500 cps to 15,000 cps; in other embodiments, the viscosity is 2,000 cps to 4,000 cps. For example, the viscosity of the second slurry can be 500 cps, 1,000 cps, 2,000 cps, 3,000 cps, 4,000 cps, 5,000 cps, 8,000 cps, 11,000 cps, 13,000 cps or 15,000 cps.
[0040] In this article, the specific test method for viscosity is: take an appropriate amount of the slurry to be tested and place it in the test tank of the cone-plate viscometer, select the 51# rotor for the test rotor, set the measuring speed to 30 rpm, set the water bath temperature to 25°C, start the measurement, and read the viscosity value after the measurement is completed.
[0041] In some embodiments, the first slurry and the second slurry each independently include an active material, a binder, a conductive agent, a dispersant, and a solvent.
[0042] In some embodiments, the dispersant includes at least one of sodium lauryl sulfate and fatty alcohol polyoxyethylene ether, thereby improving the dispersibility of the slurry and improving the viscosity of the slurry.
[0043] In some embodiments, based on the mass of the first slurry or the second slurry, the mass content of the dispersant is 0.2% to 0.4%, for example, 0.2%, 0.3% or 0.4%.
[0044] In some embodiments, the coating includes at least one of blade coating, roller transfer coating, slot extrusion coating, and double-layer extrusion coating. As an example, a double-layer coating die can be used to simultaneously coat the first coating and the second coating (for specific operations, refer to Figure 2 ).
[0045] S2: Drying the first coating layer and the second coating layer so that the first coating layer and the second coating layer together form an active material layer to obtain the electrode sheet.
[0046] In some embodiments, the drying temperature is 50°C to 140°C, for example, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C or 140°C, etc., and can be carried out in an oven. This helps to increase the drying rate, thereby forming an active material layer.
[0047] The present application prepares the pole piece by gradiently setting the solid content of the slurry so that the solvent volatilization rate in the coating layer during the drying process can be uniform, thereby increasing the surface density of the pole piece while making it less likely to crack.
[0048] The pole piece process prepared by the method described in this application is slightly different from the existing process. The slurry preparation can be directly prepared using existing equipment. The double-layer coating technology is also a relatively mature coating technology. There is no need to change the process flow, and the production efficiency is not affected. At the same time, the pole piece preparation method of this application has a wide range of applications and can be used to improve the drying abnormality of the pole pieces coated in the positive and negative electrode systems. Combined with the binder, material particle size, gradient distribution and other methods, it can be perfectly compatible with the existing double-layer coating to improve performance goals.
[0049] The second aspect of the present application provides a pole piece, which is prepared by the method described in the first aspect of the present application. Figure 1 The pole piece includes: a current collector 1, a first coating 2, and a second coating 3. Therefore, the pole piece is not prone to cracking while the surface density of the pole piece is increased.
[0050] The third aspect of the present application provides a battery, comprising a pole piece prepared by the method described in the first aspect of the present application or a pole piece described in the second aspect of the present application. Thus, the battery has a higher energy density.
[0051] It can be understood that there is no special restriction on the specific type of the battery, which can be a primary battery or a secondary battery; the shape of the battery can be a cylindrical battery, a square battery or a battery of any other shape, etc.; and according to the outer packaging classification, the battery can be a hard shell battery, a soft pack battery, etc.
[0052] Typically, a battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator, wherein the positive electrode sheet, the negative electrode sheet and the separator can be made into an electrode assembly by winding or lamination process, and the electrode assembly and the electrolyte can be contained in an outer package. Taking lithium-ion batteries as an example, during the battery charging and discharging process, active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting active ions between the positive electrode sheet and the negative electrode sheet. The separator is arranged between the positive electrode sheet and the negative electrode sheet, which mainly plays the role of preventing the positive and negative electrodes from short-circuiting, and at the same time allows active ions to pass through.
[0053] In some embodiments, the positive electrode sheet may include a positive electrode current collector and a positive electrode active material layer disposed on at least one side of the positive electrode current collector, the positive electrode active material layer including a positive electrode active material, a conductive agent and a binder, and the positive electrode current collector may include a metal foil, for example, the metal foil may be an aluminum foil. The positive electrode active material may include lithium nickel cobalt manganese oxide (NCM811), lithium nickel cobalt manganese oxide (613), lithium cobalt oxide, lithium iron phosphate, lithium manganese oxide, lithium nickel manganese oxide, lithium-rich manganese-based materials or positive electrode active materials commonly used in the art. The conductive agent may include acetylene black, single-walled carbon nanotubes and conventional materials in the art. The binder may be polyvinylidene fluoride (PVDF) and conventional materials in the art.
[0054] In some embodiments, the negative electrode sheet may include a negative electrode current collector and a negative electrode active material layer disposed on at least one side of the negative electrode current collector, the negative electrode active material layer may include a negative electrode active material, a thickener, a conductive agent and a binder, wherein the negative electrode current collector may be a metal foil, for example, the metal foil may be a copper foil. The negative electrode active material may include artificial graphite, natural graphite, a silicon-containing carbon-based composite material, a lithium-containing metal composite material, a lithium metal material and a common negative electrode active material in the art. The thickener may be a thickener sodium carboxymethyl cellulose (CMC-Na) and a conventional material in the art. The conductive agent may be acetylene black and a conventional material in the art. The binder may be styrene-butadiene rubber and a conventional material in the art.
[0055] In some embodiments, the separator can be a separator known in the art that can be used in lithium-ion batteries and is stable to the electrolyte used, such as a polyethylene separator, a polypropylene separator, a polyethylene / polypropylene composite separator, and the like.
[0056] The fourth aspect of the present application provides an electrical device, comprising the battery described in the third aspect of the present application. The electrical device has all the features and advantages of the battery described above, which will not be described one by one here.
[0057] According to an embodiment of the present application, the battery can be used as a power source for the electric device, or as an energy storage unit for the electric device. The electric device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.
[0058] The embodiments of the present application are described in detail below.
[0059] In the following Examples 1 to 3 and Comparative Examples 1 to 2, the negative electrode sheet was prepared by the following method:
[0060] (1) The negative electrode slurry is a graphite slurry with a solid content of 56% prepared by solid matter mass percentages of 96.0% graphite, 1.2% sodium carboxymethyl cellulose CMC, 1.2% styrene-butadiene rubber SBR, 1.6% carbon black and part of pure water;
[0061] (2) The negative electrode slurry is evenly coated on the current collector using a coating technique and dried with hot air to form a surface density of 230 mg / cm 2 The negative electrode.
[0062] Example 1
[0063] (1) The first slurry uses a high solid content slurry such as a lithium iron phosphate slurry with a solid content of 65% prepared by solid matter weight percentages of 96.7% lithium iron phosphate, 0.8% carbon black, 0.4% carbon nanotubes, 1.8% polyvinylidene fluoride, 0.3% sodium lauryl sulfate and fatty alcohol polyoxyethylene ether and part of N-methylpyrrolidone, and the viscosity is controlled at 4000cps;
[0064] (2) The second slurry uses a low-solid content slurry such as a lithium iron phosphate slurry with a solid content of 60% prepared by solid matter weight percentages of 97% lithium iron phosphate, 0.8% carbon black, 0.4% carbon nanotubes, 1.8% polyvinylidene fluoride and part of N-methylpyrrolidone, and the viscosity is controlled at 4000 cps;
[0065] (3) Use double-layer extrusion coating technology to coat the above two slurries to a surface density of 500 mg / cm 2 The positive electrode;
[0066] (4) After coating, drying is performed in an oven at 120°C;
[0067] (5) Assemble the prepared positive electrode sheet, negative electrode sheet, electrolyte and separator into a lithium-ion battery.
[0068] Example 2
[0069] (1) The first slurry uses a high solid content slurry such as a lithium iron phosphate slurry with a solid content of 60%, which is prepared by solid matter weight percentages of 96.7% lithium iron phosphate, 0.8% carbon black, 0.4% carbon nanotubes, 1.8% polyvinylidene fluoride, 0.3% sodium lauryl sulfate and fatty alcohol polyoxyethylene ether and part of N-methylpyrrolidone, and the viscosity is controlled at 4000cps;
[0070] (2) The second slurry uses a low-solid content slurry such as a lithium iron phosphate slurry with a solid content of 55% prepared by solid matter weight percentages of 97% lithium iron phosphate, 0.8% carbon black, 0.4% carbon nanotubes, 1.8% polyvinylidene fluoride and part of N-methylpyrrolidone, and the viscosity is controlled at 4000cps;
[0071] (3) Use double-layer extrusion coating technology to coat the above two slurries to a surface density of 500 mg / cm 2 The positive electrode;
[0072] (4) After coating, drying is performed in an oven at 120°C;
[0073] (5) Assemble the prepared positive electrode sheet, negative electrode sheet, electrolyte and separator into a lithium-ion battery.
[0074] Example 3
[0075] (1) The first slurry uses a high solid content slurry such as a lithium iron phosphate slurry with a solid content of 55% prepared by solid matter weight percentages of 96.7% lithium iron phosphate, 0.8% carbon black, 0.4% carbon nanotubes, 1.8% polyvinylidene fluoride, 0.3% sodium lauryl sulfate and fatty alcohol polyoxyethylene ether and part of N-methylpyrrolidone, and the viscosity is controlled at 4000cps;
[0076] (2) The second slurry uses a low-solid content slurry such as a lithium iron phosphate slurry with a solid content of 50% prepared by solid matter weight percentages of 97% lithium iron phosphate, 0.8% carbon black, 0.4% carbon nanotubes, 1.8% polyvinylidene fluoride and part of N-methylpyrrolidone, and the viscosity is controlled at 4000cps;
[0077] (3) Use double-layer extrusion coating technology to coat the above two slurries to a surface density of 500 mg / cm 2 The positive electrode;
[0078] (4) After coating, drying is performed in an oven at 120°C;
[0079] (5) Assemble the prepared positive electrode sheet, negative electrode sheet, electrolyte and separator into a lithium-ion battery.
[0080] Comparative Example 1
[0081] (1) The slurry is a lithium iron phosphate slurry with a solid content of 60% prepared by solid matter mass percentages of 97% lithium iron phosphate, 0.8% carbon black, 0.4% carbon nanotubes, 1.8% polyvinylidene fluoride and part of N-methylpyrrolidone, and the viscosity is controlled at 4000cps;
[0082] (2) Use a single-layer extrusion coating technique to coat the above slurry to a surface density of 500 mg / cm 2 The positive electrode;
[0083] (3) After coating, drying is performed in an oven at 100°C;
[0084] (4) Assemble the prepared positive electrode sheet, negative electrode sheet, electrolyte and separator into a lithium-ion battery.
[0085] Comparative Example 2
[0086] (1) The slurry is a lithium iron phosphate slurry with a solid content of 63% prepared by solid matter weight percentages of 97% lithium iron phosphate, 0.8% carbon black, 0.4% carbon nanotubes, 1.8% polyvinylidene fluoride and part of N-methylpyrrolidone, and the viscosity is controlled at 4000cps;
[0087] (2) Use a single-layer extrusion coating technique to coat the above slurry to a surface density of 500 mg / cm 2 The positive electrode;
[0088] (3) After coating, drying is performed in an oven at 100°C;
[0089] (4) Assemble the prepared positive electrode sheet, negative electrode sheet, electrolyte and separator into a lithium-ion battery.
[0090] The test method is as follows:
[0091] The above lithium-ion battery is discharged at a constant current of 0.33C to a cut-off voltage of 2.8V, left for 1h, and charged at a constant current and constant voltage of 0.33C with a cut-off voltage and a cut-off current of 4.2V and 0.05C respectively. The average discharge capacity obtained after three cycles is the initial capacity Q. The battery is then charged and discharged at 1C / 1C to observe the battery capacity retention, wherein the calculation formula used is as follows: Capacity retention rate (%) = Q / Q0×100%.
[0092] Table 1 Appearance and electrical performance test results of the batteries prepared in the examples and comparative examples
[0093] Pole coating status Initial capacity (Ah) 500 cycles capacity retention rate (%) Example 1 No cracking 14.2 93.40% Example 2 No cracking 14.3 93.60% Example 3 No cracking 14.2 93.10% Comparative Example 1 Cracking 13.9 91.50% Comparative Example 2 Cracking 14.0 92.10%
[0094] Depend on Figure 3 to Figure 7 The results in the pictures and Table 1 show that:
[0095] The surface of the positive electrode sheet coated by the double-layer coating method of the upper layer of low solid content slurry and the lower layer of high solid content slurry is in good condition (refer to Figures 3 to 5 ), there is no cracking, while the comparative example uses a single layer of slurry coating and all cracks occur (refer to Figures 6-7 ); and there is no significant difference in the initial capacity of the tested battery cell performance and the conventionally coated battery cell (Comparative Examples 1 to 2), and the 500-time capacity retention rate of Examples 1 to 3 is better than that of Comparative Examples 1 to 2 as a whole.
[0096] In the description of the present application, it should be understood that the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include at least one of the features. In the description of the present application, "plurality" means at least two, such as two, three, etc., unless otherwise clearly and specifically defined.
[0097] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example" or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0098] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present application.
Claims
1. A method for preparing a pole piece, characterized in that: include: Coating the first slurry and the second slurry simultaneously on at least one side of the current collector to obtain a first coating layer and a second coating layer; Drying the first coating layer and the second coating layer so that the first coating layer and the second coating layer together form an active material layer to obtain the electrode sheet; Wherein, the difference between the solid content of the first slurry and the solid content of the second slurry is 3% to 7%.
2. The method according to claim 1, characterized in that The solid content of the first slurry is in the range of 45% to 75%, preferably 55% to 65%, and the viscosity is in the range of 1000 cps to 20000 cps, preferably 4000 cps to 8000 cps.
3. The method according to claim 1, characterized in that: The solid content of the second slurry is in the range of 40% to 70%, preferably 50% to 60%, and the viscosity is in the range of 500 cps to 15000 cps, preferably 2000 cps to 4000 cps.
4. The method according to claim 1, characterized in that: The difference between the solid content of the first slurry and the solid content of the second slurry is 5%.
5. The method according to claim 1, characterized in that: The first slurry and the second slurry independently include active material, binder, conductive agent, dispersant and solvent.
6. The method according to claim 5, characterized in that Satisfy at least one of the following conditions: The dispersant includes at least one of sodium lauryl sulfate and fatty alcohol polyoxyethylene ether; Based on the mass of the first slurry or the second slurry, the mass content of the dispersant is 0.2% to 0.4%.
7. The method according to claim 1, characterized in that The coating comprises at least one of blade coating, roller transfer coating, slot extrusion coating, and double-layer extrusion coating; and / or The drying temperature is 50°C to 140°C.
8. A pole piece prepared by the method according to any one of claims 1 to 7.
9. A battery, characterized in that: The invention comprises a pole piece prepared by the method according to any one of claims 1 to 7 or a pole piece according to claim 8.
10. An electrical device, characterized in that: A battery comprising the battery of claim 9.